Prototype of a Virtual Experiment Information System for the Mont Terri Underground Research Laboratory - Graebling, Nico; Şen, Özgür Ozan; Bilke, Lars; Cajuhi, Tuanny; Naumov, Dmitri; Wang, Wenqing; Ziefle, Gesa; Jaeggi, David; Maßmann, Jobst; Scheuermann, Gerik; Kolditz, Olaf; Rink, Karsten (Frontiers in Earth Science, 2022)
Underground Research Laboratories (URL) allow geoscientific in-situ experiments at large scale. At the Mont Terri URL in Switzerland, international research groups conduct numerous experiments in parallel. The measured and simulated data as well as research results obtained from them are highly relevant as they improve the general understanding of geological processes, for example in the context of radioactive waste disposal. Unfortunately, the data obtained at the test site is often only available to researchers who are directly involved in a particular experiment. Furthermore, typical visualisation techniques of such data by domain scientists often lack spatial context and accessing and exploring the data requires prior technical knowledge and a high level of effort. We created a digital replica of the Mont Terri URL and thereby implemented a prototype of a Virtual Experiment Information System that integrates highly heterogeneous data from several different sources. It allows accessing and exploring the relevant data embedded in its spatial context without much prior technical knowledge. Both, simulation results and observation data are displayed within the same system. The 4D visualisation approach focuses on three exemplary experiments conducted at Mont Terri and is easily transferable to other experiments or even other URLs. The Unity Game Engine has been used to develop the prototype. This allowed to build the application for various output devices like desktop computers or Virtual Reality hardware without much additional effort. The implemented system reduces the technical effort required to access and explore highly relevant research data and lowers the cognitive effort usually needed to gain insights from measurements, simulation models and context data. Moreover, it promotes exchange among research groups by enabling interactive visualisations embedded in the URL's spatial context. In addition, a future use of the system for the communication of scientific methods and results to stakeholders or the general public is plausible.